2007
DOI: 10.1044/1092-4388(2007/016)
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Selected Lexical Factors on Confrontation Naming Accuracy, Speed, and Fluency in Adults Who Do and Do Not Stutter

Abstract: Results suggest that AWS could have a fundamental deficit in lexical retrieval, but this deficit is unlikely to be at the level of the word's abstract phonological representation. Implications for further research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
4
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 70 publications
8
65
4
3
Order By: Relevance
“…Prins et al (1997) observed a larger effect of word frequency on picture naming RT in PWS compared to controls, suggesting word form access and retrieval is less efficient in PWS. A similar finding has been reported by Newman and Bernstein Ratner (2007). Deficits in lexical selection and accessing lexical phonology cannot be the sole cause of stuttering, though; Packman, Onslow, Coombes, and Goodwin (2001) observed significant amounts of stuttering by three PWS when reading aloud written texts composed of non-words.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Prins et al (1997) observed a larger effect of word frequency on picture naming RT in PWS compared to controls, suggesting word form access and retrieval is less efficient in PWS. A similar finding has been reported by Newman and Bernstein Ratner (2007). Deficits in lexical selection and accessing lexical phonology cannot be the sole cause of stuttering, though; Packman, Onslow, Coombes, and Goodwin (2001) observed significant amounts of stuttering by three PWS when reading aloud written texts composed of non-words.…”
Section: Introductionsupporting
confidence: 61%
“…Newman and Bernstein Ratner (2007) examined the effects of neighbourhood density and neighbourhood frequency on picture naming in adults who stutter. Both effects arguably influence the encoding of the sub-lexical content of word forms (Newman & Bernstein Ratner, 2007). Neither effect, however, distinguished PWS from fluent speaking controls.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, findings from studies of adults who stutter (AWS) have been similarly inconsistent, with some suggesting that the speech-language processing systems of AWS may be slower and/or less accurate than adults who do not stutter (e.g., Newman & Ratner, 2007;Prins, Main, & Wampler, 1997;Sasisekaran & DeNil, 2006) and others reporting no such differences (e.g., Weber-Fox, Spencer, Spruill, & Smith, 2004). Given these uncertainties, further study of the speech-language processing abilities of CWS would appear to be warranted.…”
Section: Repetition Priming and Age Of Acquisition Effects In Speech mentioning
confidence: 99%
“…In turn, small or poorly organized vocabularies limit comprehension of both oral language and written language. Another example is that individuals who inefficiently access extant phonological representations may demonstrate word finding difficulties (German & Newman, 2007) and dysfluent speech (Newman & Ratner, 2007). Individuals with imprecise phonological representations are likely to evidence articulation errors.…”
Section: Introductionmentioning
confidence: 99%